A Comparison of Exchange Rate Exposure between Manufacturing vis‐à‐vis Service Sector Firms in India1. Issue 1 (24th July 2016) - Mohapatra, Sonali Madhusmita
Abstract : This paper examines the exchange rate exposure of firms in the manufacturing and service sectors in India, and measures this exposure by considering the trade weighted exchange rate as an explanatory variable by using monthly data from January 2000 to December 2013. The results show that Indian firms were highly exposed to the exchange rate during that period. A comparison of firms in the manufacturing and service sectors showed that the degree of exposure was higher for firms in the manufacturing sector. Overall, the results suggest that firms were more vulnerable to exchange rate changes in the post‐ than pre‐crisis period.